Microfinance and Index Insurance : Testing Business Models in the Agricultural Sector - Assah, Fatou C.; Sberro-Kessler, Rachel (World Bank, Washington, DC, 2017)
While access to credit is a key instrument toalleviate rural poverty, microfinance institutions(MFIs) are often unable to expand their agriculturelending portfolio. One of the key advantages for microfinance institutions to offer index insurance products to their customersis to reduce the default risk on their agriculture lending portfolio and therefore allow the expansion of agriculture credit. Index-insurance can be sold by microfinance institutions either on a mandatory or voluntary basis.One of the key success factors of credit-bundling is to offer a holistic solution to mitigate agriculture risks. The second business model that microfinance institutions have tested is to be direct customers of index insurance. Portfolio insurance has the potential to benefit farmers both ex-post (ex: restructuring of loans, loans write-offs, offer of emergency loans) and ex-ante (ex: larger supply of agriculture credit, reduced agriculture lending interest rates).